2020
DOI: 10.3390/ma13041000
|View full text |Cite
|
Sign up to set email alerts
|

Thermoplastic Starch (TPS) Films Added with Mucilage from Opuntia Ficus Indica: Mechanical, Microstructural and Thermal Characterization

Abstract: Opuntia cladodes are a typical vegetable waste, from which mucilage in gel form can be extracted. This work proposes blending it with a self-produced thermoplastic starch (TPS), originating from potato starch with a high content in glycerol (ca. 30%). Three methods were compared for extraction, bare maceration (MA), mechanical blending (ME) and mechanical blending following maceration (MPM) to produce films with an approximate thickness of 150 μm. For the comparison, tensile testing, differential scanning calo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…This reference suggests that the plasticization effect is in the present study much more contained, as observed by the elongation at break for the pure TPS, which just exceeds 50%, making the material quite controllable and with predictable properties during use. In particular, a considerably lower deformation was measured with respect to what was observed in other studies, such as [13], on glycerol and citric acid on corn starch tensile properties. The mechanical properties of the developed films compare quite favorably with those reported in other studies, especially for what concerns the Young's modulus.…”
Section: Resultscontrasting
confidence: 68%
“…This reference suggests that the plasticization effect is in the present study much more contained, as observed by the elongation at break for the pure TPS, which just exceeds 50%, making the material quite controllable and with predictable properties during use. In particular, a considerably lower deformation was measured with respect to what was observed in other studies, such as [13], on glycerol and citric acid on corn starch tensile properties. The mechanical properties of the developed films compare quite favorably with those reported in other studies, especially for what concerns the Young's modulus.…”
Section: Resultscontrasting
confidence: 68%
“…Lastly, the cultivation of succulents could aid with global climate mitigation targets in both direct and indirect capacities, through: (i) carbon sequestration and the drawdown of CO 2 (Inglese et al, 2017) and (ii) diversion away from carbon-intensive fossil fuel energy sources and increased efficiency in the way in which land is used (Searchinger et al, 2018). The greater water-use efficiency of succulents relative to C3 or C4 plants is primarily due to the CAM photosynthetic pathway, which is more efficient in converting available water and CO 2 to plant dry matter (Han & Felker, 1997;Nobel, 1991Nobel, , 1994Nobel, , 2009, with biomass generation per unit of water approximately 5-10 times higher than in C 3 and C 4 species (Alary et al, 2007;Borland et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Others argue for a focus more on total carbon land-use efficiency (e.g. Searchinger et al, 2018) rather than marginality in terms of prioritising land use, production and global carbon stores. This study examines a series of potential ways in which 'available' lands could be defined based on changing landscapes and land uses under different socio-economic futures and/or different anticipated climate trajectories.…”
Section: 'Available' Land Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Scanning electron microscopy is a part of an electron microscope, used to evaluate the surface morphology of starch–mucilage films. Electrons are bombarded on the prepared sample through electron beams resulting in the reflection of electrons towards the object from the sample [ 41 ]. Generally, coating of film samples can be carried out with gold for evaluation of surface morphology.…”
Section: Physicochemical Properties and Characterization Of The Starch–mucilage Filmmentioning
confidence: 99%